Social media in radiology: overview and usefulness of online professional #SoMe profiles - Spieler, Bradley (Acad Radiol, 2020)
Social media is a ubiquitous part of society and used by many healthcare professionals, including radiologists. This article prepared by the 2019–2020 Radiology Research Alliance Social Media Task Force presents different uses and benefits of an online professional social media profile. Physician and healthcare-specific issues along with popular platforms such as LinkedIn, Facebook, Twitter, Instagram, and YouTube are used to explore topics including education, branding, research, mentorship, promotion, and leadership.